â€œALâ€ AL-DAKHILIYAH â€˜ALA AL-ASMAâ€™: DIRASAH TAHLILIYAH NAHWIYAH FI SURAH YASIN - Ubaidillah, Ubaidillah (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2018)
This research discusses Nahwu that can help improve the understanding of the Qur'an, especially the surah Yaasin in which the type of "Al" is studied and its functions, because most people assume â€œAlâ€ that entered onto Ism has no other types and function except for definition only. The researcher uses interpretive approach to recognize the types of "Al" and its functions. The study concludes that "Al" entering onto Ism consists of two types and the functions vary according to the different types, but the most predominant appears from the meaning of speech is not referring to the literal meaning.